A Rare Case of Glomus Tumor of the Great Toe: An Analysis of Behavior at This Rare Site. Issue 1 (February 2016) - Mohindra, Mukul; Sambandam, Balaji; Gautam, V. K.; Maini, Lalit
Glomus tumor, originally known as an angioneuromyoma, is a benign neoplasm arising from specialized structures called glomus bodies, involved in thermoregulation. Although it has been reported at a number of sites in the body, this rare tumor is most commonly seen in the subungual areas of the digits of the hand. Only a handful of lesions have been reported in the toes. Because most foot conditions are treated by podiatrists and dermatologists, orthopaedic surgeons are generally unaccustomed to making early diagnoses. The purpose of this case report is to alert the attending surgeon regarding the possibility of glomus tumor as a cause of chronic toe pain. Also it has been observed that the behavior of this tumor varies with the site of occurrence—whether digital or extradigital. So we have extensively reviewed all similar reports in the literature to analyze the behavior of this tumor at this unusual location, apart from comparing it with the more common finger variety, to ensure it possibly is not a misclassification like the chemodectomas that were earlier thought to be glomus tumors. Levels of Evidence: Therapeutic Level IV: Case Study